2020
DOI: 10.3390/f11020210
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Stock and Sequestration Potential of an Agroforestry System in Sabah, Malaysia

Abstract: Total aboveground carbon (TAC) and total soil carbon stock in the agroforestry system at the Balung River Plantation, Sabah, Malaysia were investigated to scientifically support the sustaining of natural forest for mitigating global warming via reducing carbon in the atmosphere. Agroforestry, monoculture, and natural tropical forests were investigated to calculate the carbon stock and sequestration based on three different combinations of oil palm and agarwood in agroforestry systems from 2014 to 2018. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 29 publications
(34 reference statements)
1
28
2
Order By: Relevance
“…The carbon stocks of the simple systems (i.e., combination of single trees with cash crop or grass) and mixed-tree system are slightly similar to C stock on agroforestry systems reported by other studies in Indonesia [31,32]. The C stock is found relatively higher in oil palm and agarwood-based systems in Sabah, Malaysia [34]. The mix tree plot systems in our study shows higher potential carbon stock than complex agroforestry system in the buffer zones of a national park in Sulawesi, and mixed tree systems in Bengkulu [33,35].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The carbon stocks of the simple systems (i.e., combination of single trees with cash crop or grass) and mixed-tree system are slightly similar to C stock on agroforestry systems reported by other studies in Indonesia [31,32]. The C stock is found relatively higher in oil palm and agarwood-based systems in Sabah, Malaysia [34]. The mix tree plot systems in our study shows higher potential carbon stock than complex agroforestry system in the buffer zones of a national park in Sulawesi, and mixed tree systems in Bengkulu [33,35].…”
Section: Discussionsupporting
confidence: 75%
“…In Indonesia's Bengkulu province, mixed tree agroforestry systems store around 95.2 tons ha −1 regardless of age [33]. Carbon stock storage in agroforestry systems with a combination of oil palm and agar wood vary between 78.28 and 79.13 Mg C ha −1 in regard to different levels of soil bulk density [34]. While simple and complex agroforestry systems adjacent to the Lore Lindu National Park buffer zones in Palu, Indonesia show significant differences in carbon stock.…”
Section: Introductionmentioning
confidence: 99%
“…The higher number in this study might be affected by the depth of the soil sample that has been taken which is 1 meter depth compared to the previous study (0.3 meters). However, these reports are in contrast with the study reported by Besar et al (2020) on a natural tropical forest carbon stock value. Their study shows that soil made up only 13% of the total ecosystem carbon stock while the living trees hold the most carbon with 87%.…”
Section: Aboveground Carbon Stock Belowground Carbon Stock Soil Carcontrasting
confidence: 84%
“…When compared to other agroforestry systems, the Tembawang agroforestry system stored more carbon. In a comprehensive report Besar et al, 2020), the carbon storage value of rubber plantation had higher value. In the same DBH range (≥ 10 cm), the carbon storage value in Tembawang agroforestry was in the aboveground carbon storage range of secondary tropical forests in Maluku, Indonesia with an average value of 70.3 Mg C ha -1 (Stas, 2014).…”
Section: Total Aboveground Biomass and Carbon Storagementioning
confidence: 98%